The Quarter: A Complex of Neighbourhood Units in Turkey - USTA, AYHAN; USTA, GÜLAY (My University, 2010)
In history, spatial organizations for houses have been changed and improved depending on the natural conditions, well-being of people, utilization of resourses, population density, family structure and urbanization rate. It can be said the spatial organization of housing that they are both in a relationship with culture and they are a total configuration of social, demographical, psycological, human behaviorial and environmental structure. Any housing settlement in Turkish Islamic tradition is macro and micro scaled organization in which social relation and cultural characteristics of society that are necessary for physical environment and society reflect. Basic element of urban spatial organization in Turkish Islamic housing pattern is "the quarter". (Quarter is called as "mahalle" in Turkish culture) The quarter contains functional and semantic characteristics which are common for most Islamic civilization and Turkish Islamic cities. In this study, what meaning does the quarter have as smallest spatial organization element in Anatolia will be examined. In additon what kind kind of evolutionary process does the quarter face in Turkish settlement.
Keywords: Mahalle; komşuluk ünitesi; Tradition; Turkish Housing Settlement; Neighbourhood Units; The Quarter